Comparison of the performance of multi-carrier IFSK and M-ary IFSK modulation techniques in indoor portable radio communications systems - Amca, Hasan A. (IEEE, 1995)
A transmission medium simulator based on millimeter wave propagation field measurements has been developed to study the effect of modulation index on the performance of wideband incoherent frequency shift keying (WIFSK), the best value of M for M-ary IFSK (MIFSK) and the multicarrier modulation (MCM)/IFSK techniques that will increase the transmission rate of indoor portable radio communications (IPRC) systems against intersymbol and interchannel interferences. Carrier separation is introduced into the MCM/incoherent minimum shift keying (IMSK) system and system performance is evaluated as a function of the carrier separation. WIFSK and MIFSK systems offer no advantage over IMSK and pulse shaping does not increase bandwidth efficiency significantly.
Proceedings of the 1995 4th IEEE International Conference on Universal Personal Communications Record --
Keywords: Carrier communication; Communication channels (information theory); Electromagnetic wave propagation; Frequency shift keying; Intersymbol interference; Radio communication; Radio transmission; Incoherent minimum shift keying (IMSK); Indoor portable radio communications systems; Interchannel interference (ICI); M ary incoherent frequency shift keying (MIFSK); Millimeter wave propagation field measurements; Modulation index; Multicarrier modulation (MCM); Orthogonal frequency division multiplexing (OFDM); Wideband coherent frequency shift keying (WIFSK); Mobile radio systems